Xylem Limited Bacteria (XLB) Clove Disease Control Technology Through Utilization of Endophytic Bacteria - Chrisnawati, Chrisnawati; Nasrun, Nasrun; Yulfidesi, Yulfidesi; Suryani, Suryani; Kasmawati, Kasmawati (Akta Agrosia, 2022)
Xylem Limited Bacterium  (XLB) disease  (Ralstonia syzygii) is  the most seriuos disease on clove plant. Biological control using Endophytic Bacteria (Bacillus sp. Bc25 and Fluorescentpseudomonad Pf22) is expected to control clove XLB disease.The  research  aim to get  Bacillus sp. Bc25 and   Fluorescent pseudomonad Pf22product are effective to control XLB disease on clove plant.The study of Bacillus sp. Bc25 and Fluorescent pseudomonad Pf22 was done in watering  on clove plant  field were infected by XLB disease in Solok West Sumatera on January to December 2017.The study used a randomized block design (RBD) with four replications. The parameters observed were the disease attack level and plant growth.The study results showed thatBacillus sp.Bc25  andFluorescentpseudomonadPf 22 can control  XLB  disease and increase clove growth.Bacillus sp. Bc25 and Fluorescentpseudomonad Pf22 combinationdemonstrate XLB   disease control capabilities and promote the best clove plants  growthby intensity suppressing of XLB  disease from 86.80% to 20.59% and increasing the clove plants growth from the stem circle 20.00 cm to 46.00 cm.Combination product of biological agents Bacillus sp. Bc25 and FluorescentpseudomonadPf22 can be developed to control XLB  diseases and increase clove plant growth.Keywords : Clove, Xylem Limited Bacteria Disease (Ralstonia syzygii),        Endophytic Bacteria (Bacillus sp. Bc25 and Fluorescent pseudomonad Pf22.